The effectiveness of portfolio assessment based problem based learning on mathematical critical thinking skills in elementary schools - Darmiyati, Darmiyati; Sunarno, Sunarno; Prihandoko, Yogi (Trigin Institute, 2023)
This study aims was determine the effectiveness of the problem-based learning model based on portfolio assessment on the ability to critical thinking in mathematics. The research sample was 120 elementary school students in South Kalimantan. sampling was used multistage cluster sampling technique. This research was a quasiexperimental research. Data analysis was performed used a two-way ANACOVA test. The results showed that (1) Problem based learning had an influence on students' critical thinking skills in mathematics because the Fcount obtained was 6.351 compared to F table (0.05< 1.115), which was 3.93. (2) it was said that there was a significant influenced between the interaction of learning models and assessment techniques on students' critical thinking skills in mathematics because the Fcount obtained was 25.669 compared to Ftable (0.05< 1.115), namely 3.93. (3) it was not true that the portfolio assessment technique has a significant effect on students' mathematical critical thinking skills. The Fcount obtained was 1.476 compared to Ftable (0.05>1.115), which was 3.93. Judging from the value of sig. (0.227) > α (0.05)